A study of apparent quantum efficiency in different structures of cadmium telluride solar cells. (June 2017) - Jiang, Yanan; Hu, Dingqin; Tang, Peng; Zhang, Jingquan; Liu, Cai; Wang, Wenwu; Zeng, Guanggen; Wu, Lili; Li, Wei; Feng, Lianghuan
Highlights: Investigated the impact of SnO2 and CdS layer on carrier collection mechanism. Established connections between apparent quantum efficiency and device structures. The existence of SnO2 generates a large phase shift in shortwave spectral response. Abstract: In recent years, the power conversion efficiency (PCE) up to 20% was obtained based on CdTe solar cells consisting of Glass/SnO2 : F/SnO2 /CdS/CdTe/ZnTe: Cu/Au. The underlying carrier transport and collection mechanisms of this architecture become complicated while quantum efficiency with external direct current bias is tremendously informative. Quantum efficiency measurement under forward voltage changes dramatically and it is defined as apparent quantum efficiency (AQE). It is accessible to give insight to the impact of the high resistant transparent buffer layer and CdS window layer on the carrier collection mechanism and photocurrent loss. Herein, five simpler structures were fabricated and tested together with the structure mentioned above for both direct current (DC) and alternating current (AC) modes of quantum efficiency under forward bias and four types (470 nm, 525 nm, 780 nm, 850 nm) of monochromatic light to achieve a pair of I-V curves under different light intensities. Comparing the AQE acquired via applying various forward bias with different device structures along with their collection efficiency of different wavelength, it is available to establish the connection between AQE effects and device structures. The consistent tendency of the AQE response under DC mode at forward bias for different structures of CdTe devices indicates a same current direction without phase shift. While the introduction of SnO2 buffer layer is prone to generate a large phase angle in the shortwave AQE response, resulting in AQE > 1. When there is no photoconductive CdS layer, the device photocurrent under forward bias changes slightly and uniformly in the measured spectra, avoiding intricate band diagram in the CdS region.